2020
DOI: 10.1016/j.heliyon.2020.e04551
|View full text |Cite
|
Sign up to set email alerts
|

Improper disposal practice of unused and expired pharmaceutical products in Indonesian households

Abstract: Background Improperly disposed medicines could adversely affect the environment and increase the risk of drug misuse or accidental poisoning. Objective To evaluate the disposal practices of unused and expired medicines among the general population in Bandung, Indonesia. Method This was a descriptive cross-sectional survey conducted among 497 respondents in Bandung, Indonesia. Data were collected through interviews using a prevalidated structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
55
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 29 publications
8
55
1
8
Order By: Relevance
“…This also agrees with ndings in Brazil [49] and Ethiopia [26,27]. [26,28]. Also, antimalarial, analgesics and antibiotics were predominantly stored by households.…”
Section: Attitude On Expiry and Disposal Of Expired And Unused Medicasupporting
confidence: 91%
See 4 more Smart Citations
“…This also agrees with ndings in Brazil [49] and Ethiopia [26,27]. [26,28]. Also, antimalarial, analgesics and antibiotics were predominantly stored by households.…”
Section: Attitude On Expiry and Disposal Of Expired And Unused Medicasupporting
confidence: 91%
“…Medicines expiry is the date provided on them that guarantees their full potency and safety under good manufacturing practices and several of them, such as vaccine vials, insulin and nitro-glycerin degenerate on expiry [47,48]. Our study revealed that many households con rmed medicines expiry on prescription and OTC drugs, as previously reported [7,9,25,28]. This could be attributed to the awareness created over the years on the need to ensure that medicines are still within the expiry dates before use.…”
Section: Attitude On Expiry and Disposal Of Expired And Unused Medicasupporting
confidence: 65%
See 3 more Smart Citations